Draping as a technique to develop creative skills in Saudi Arabian fashion design Drapeado como una técnica para desarrollar habilidades creativas en el diseño de moda en Arabia Saudita - Nasser-Alajaji, Tahani; Abdullah-Alqudairi, Tahani (Arte, Individuo y Sociedad, 2018)
This study aims at studying the effect of fashion design’s draping method on a dress form in developing creative skills(Originality, Fluency, Flexibility, The details).This study followed an experimental approach and used a variety of methods and tools to collect the scientific material of the study, The following tools were included: Pre- and post- skills tests, assessment scale to evaluate the designs and observation. The sample size of the study was 75 female students in the experimental group and 30 female students in the control group among the female students of the College of Arts and Design at PNU .The total number of designs was 150 design for the experimental group and 60 for the control group. It was presented and arbitrated by six arbitrators. The total number of questionnaires before and after the applied program was 900 questionnaires for the experimental group and the control group was 360, and they were analyzed statistically. The study arrived at the following results: the design of a series of innovative outfits using the draping method on a dress form. also confirmed that technical performance in dress form draping improves the designers’ creative skills development, which then helps them to implement innovative designs.